THE BENEFIT OF USING DICTATION METHOD IN ZOOM MEETING TO IMPROVE STUDENTS’ WRITING SKILL (Karya Ilmiah Mahasiswa (KIMA), 2024)
The aim of this study was to find out the advantage of using dictating methods on the Zoom Meeting app to improve students’ writing skills. This type of research is survey research approach using descriptive design. The population in this survey includes all fourth semester students of English Language Education at Muslim University Indonesia. Samples from this study were taken using the Total Sampling technique, which means that all populations were used as a sample of 37 Students. In data collection, the instrument used is a closed anglet. The results of the research showed that there were no constraints perceived in Students with this method, seen from the statement no. 3 “Relevant Zoom Meeting app is used to improve student writing skills in dictating methods” and data showed 35.1% Students chose to agree, 27% Students opted to doubt – doubt, 16.2% Students voted to disagree and 16.2% Student voted strongly disagreed. From the output, some Students are unlikely to have trouble using dictating methods on the Zoom Meeting app as a medium to improve writing skills.